2015
DOI: 10.1038/srep18332
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of serum interleukin-18 in predicting cardiovascular mortality in patients with chronic kidney disease – systems and clinical approach

Abstract: The aim of this study was to check if serum interleukin-18 (IL-18) predicts 2-year cardiovascular mortality in patients at various stages of chronic kidney disease (CKD) and history of acute myocardial infarction (AMI) within the previous year. Diabetes mellitus was one of the key factors of exclusion. It was found that an increase in serum concentration of IL-18 above the cut-off point (1584.5 pg/mL) was characterized by 20.63-fold higher risk of cardiovascular deaths among studied patients. IL-18 serum conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 29 publications
(37 reference statements)
1
39
0
3
Order By: Relevance
“…IL18 seems to be important indicator and predictor of cardiovascular death in two-year follow-up among non-diabetic patients suffering from chronic kidney disease, with a history of acute myocardial infarction in the previous year. The importance of IL-18 in the process of atherosclerotic plaque formation has been confirmed by systems analysis based on a formal model expressed in the language of Petri nets theory [50].…”
Section: Discussionmentioning
confidence: 88%
“…IL18 seems to be important indicator and predictor of cardiovascular death in two-year follow-up among non-diabetic patients suffering from chronic kidney disease, with a history of acute myocardial infarction in the previous year. The importance of IL-18 in the process of atherosclerotic plaque formation has been confirmed by systems analysis based on a formal model expressed in the language of Petri nets theory [50].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, in one study it was confirmed that young and middleaged patients with a recent AMI have higher IL-18 concentration in serum than age-and sex-matched control subjects, showing that concentration of this cytokine is associated with severity of coronary atherosclerosis [100]. In addition, recent evidence suggests that serum IL-18 is an important indicator and predictor of CV death in two-year follow-up among nondiabetic patients suffering from CKD, with history of AMI in the previous year [101].…”
Section: Renal Biomarkersmentioning
confidence: 73%
“…Chiang,et al 13) demonstrated that hemodialysis patients with high levels of IL-18 had a higher probability of hospitalization event during the follow-up period. In another study, Formanowicz, et al 6) found that serum IL-18 concentration was increased in various stages of CKD. IL-18 was found to be superior to well-known cardiovascular risk parameters, such as hs-CRP, carotid intima media thickness, glomerular filtration rate, albumins, ferritin, and N-terminal prohormone of brain natriuretic peptide, in the prognosis of cardiovascular mortality in CKD.…”
Section: Discussionmentioning
confidence: 91%
“…The hemodialysis patients had significant higher levels of IL-18 than healthy controls (701. 6 88.52 versus 152.0 55.31 pg/mL, P < 0.01). Furthermore, SBP, DBP, creatinine, and hs-CRP were significantly higher and LVEF was significantly lower in hemodialysis patients (P < 0.01) than in healthy controls.…”
Section: Demographic and Clinical Characteristics Of Enrolled Particimentioning
confidence: 88%
See 1 more Smart Citation